An Application of Porter’s Five Forces on Sports Goods Cluster at Jalandhar, Punjab - Jhamb, Priya (Gyan Management Journal, 2014)
The paper attempts to analyze the intensity of competition within sports9oods cluster of]alandhar on the basis of Porter’s five forces model. The study indicates thatjalandhar cluster is a market leader in sports goods sector in India yet it has strong rivals. Further, threat of new entrants and bargaining power of supplier is moderate while threat of substitute goods, bargaining power of customers and rivalry among the existing firms is strong.